Analisis Responsivitas Pelayanan Publik dalam Menanggapi Pengaduan Masyarakat pada Penggunaan Aplikasi Wargaku Surabaya - Maha, Nina Karina; Dewi, Maharani Adiza; Amanda, Stephanie Tri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
With the development of information and communication technology (ICT), the concept of smart management has transformed public services. The Wargaku Surabaya application aims to enhance the efficiency and responsiveness of public services. This study aims to evaluate how public services address community complaints through the Wargaku application using six responsiveness indicators: staff attitude, accuracy, speed, thoroughness, timeliness, and the ability to respond to complaints. A descriptive qualitative method was employed to collect data through interviews, observations, and documentation. The Wargaku application successfully meets all six responsiveness criteria. Public service staff are friendly; the document validation process adheres to standards; services are provided quickly and thoroughly, and most requests are handled on time. Additionally, staff address community complaints both directly and through the application. This success stems from the government’s commitment to delivering high-quality public services and effective technology integration. The Wargaku application serves as a potential model for other regions due to its efficient system and experienced personnel. It also significantly contributes to the development of smart governance in Surabaya.